2013
DOI: 10.13080/z-a.2013.100.015
|View full text |Cite
|
Sign up to set email alerts
|

Leaching of base cations as affected by a forty-year use of mineral fertilisation

Abstract: A long-term crop rotation experiment was established in Central Lithuania (Skėmiai, Radviliškis region) in 1971 (lysimeters were installed in 1976) on a sandy loamy Endocalcari-Endohypogleyic Cambisol (CMg-n-w-can). The effect of regular fertilisation with different rates and combinations of NPK fertilisers in a crop rotation (winter wheat → sugar beet → spring barley → spring rape → annual grasses and perennial grasses) on the concentrations of cations (Ca , respectively. Low levels of potassium leaching had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…Liming of acid soils is a world-wide practice in agriculture (Adomaitis et al, 2013;Paradelo et al, 2015;Litvinovich et al, 2017;Holland et al, 2018) aimed to reduce soil acidity and to replenish leached out soil cations. ZEMLJISTE I BILJKA,VOL.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Liming of acid soils is a world-wide practice in agriculture (Adomaitis et al, 2013;Paradelo et al, 2015;Litvinovich et al, 2017;Holland et al, 2018) aimed to reduce soil acidity and to replenish leached out soil cations. ZEMLJISTE I BILJKA,VOL.…”
Section: Introductionmentioning
confidence: 99%
“…68,No. 1,[1][2][3][4][5][6][7][8][9][10][11][12] From all the cations migrating in soil, calcium is the most mobile one (Litvinovich et al, 2012;Adomaitis et al, 2013;Fernández-Sanjurjo, 2014;Goulding, 2016). In humid climate the main cause of calcium losses is a vertical migration with atmospheric precipitations (Kopáček et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gransee and Führs (2013) reported that exchangeable Mg is readily mobile in the soil in comparison to other cations and is greatly influenced by the presence of Ca, K, and NH 4 . Being weakly bound to silicate clay minerals as well as SOM, soil solution Mg concentrations tend to be larger than that of other cations and increase with the addition of Ca 2+ and K + (Adomaitis et al., 2013; Litvinovich et al., 2021; Mikkelsen, 2011). The enhanced mobility of Mg in neutral to acidic soil, which characterizes the soils used in this study, tends to limit Mg retention (Yan & Hou, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…As an example, incentives for purchasing N fertilizers in China has led to severe soil acidification and exchangeable Ca and Mg losses (Guo et al, 2010). Regarding such concerns, Adomaitis et al (2013) highlighted in a long-term trial in a sandy soil that greater fertilization to achieve high cash crop yields resulted in high Ca and Mg losses, 360 and 67 kg ha -1 yr -1…”
Section: Introductionmentioning
confidence: 99%